Pola Pemetaan Distribusi Air Lindi Pada Kualitas Air Permukaan Di Kawasan TPA Kandis Kabupaten OKU - Lucyana Lucyana; Eka Rizki Meiwinda; Tommy Romansyah (Jurnal Media Infotama, 2023)
The quality and quantity of groundwater can decrease, one of the causes is the waste management carried out at the Final Waste Management Site (TPA). . The values of Fe, Cd, Cr, NO2, and Zn at station 1 were above the BML values, while the values of Fe, Cd, Zn and Pb at station 2 while the values of Cd, Zn and Pb at station 3 were above the recommended BML values. The waste in the Simpang Kandis TPA has not been properly managed, causing leachate to spread to the environment around the Simpang Kandis TPA.